Chapter 8 A European field of public administration? Administrative cooperation of asylum agencies in the Dublin system - Lahusen, Christian (Taylor & Francis, 2019)
The European Union started to coordinate and harmonise the asylum policies of their Member States in 1999 within a common 'area of freedom, security and justice', as stipulated by the Treaty of Amsterdam. However, the communitarisation of asylum policies by the EU has not met its main targets, despite the installation of the Common European Asylum System (CEAS) and several attempts to implement and improve these regulations and directives by means of legislative reforms, political programmes and administrative initiatives. Today, we are still far from a European-wide asylum regime that implements harmonised procedures, and grants equivalent protection titles across all Member States (Council of the European Union, 2016a). National asylum systems and recognition rates continue to differ widely within the EU (AIDA, 2017; EASO, 2017a).